2017
DOI: 10.1101/162297
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GPS2 regulates mitochondria biogenesis via mitochondrial retrograde signaling and chromatin remodeling of nuclear-encoded mitochondrial genes

Abstract: 2 SummaryAs most of the mitochondrial proteome is encoded in the nucleus, mitochondrial functions critically depend on nuclear gene expression and bidirectional mito-nuclear communication. However, mitochondria-to-nucleus communication pathways are incompletely understood. Here, we identify G-Protein Pathway Suppressor 2 (GPS2) as a mediator of mitochondrial retrograde signaling and a key transcriptional activator of nuclear-encoded mitochondrial genes in mammals. GPS2 regulated translocation from mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 103 publications
2
6
0
Order By: Relevance
“…We found that Hsp60 and TFAM levels were similar, however GPS2 was elevated in perinuclear regions, consistent with its role as nuclear transcription factor28. In patient muscle, compared to perinuclear COX-positive areas, Hsp60 (2.2-fold), GPS2 (1.2-fold), and TFAM (1.5-fold) levels were all higher in COX-deficient niches.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…We found that Hsp60 and TFAM levels were similar, however GPS2 was elevated in perinuclear regions, consistent with its role as nuclear transcription factor28. In patient muscle, compared to perinuclear COX-positive areas, Hsp60 (2.2-fold), GPS2 (1.2-fold), and TFAM (1.5-fold) levels were all higher in COX-deficient niches.…”
Section: Resultssupporting
confidence: 69%
“…Our data in human skeletal muscle suggests a role for the UPR mt and possibly implicates other factors such as GPS2, which transcriptionally activates mitochondrial biogenesis in response to mitochondrial stress or depolarization32. Beclin1 labelling suggests no change in mitophagy in small foci.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In light of the absent homology of the RTG genes in higher eukaryotes, mitochondrial communication with the nucleus is evidently far more complex, especially in mammals that deploy different executors for various mitochondrial stressors. Those identified, to date, encompass transcription factors (e.g., GPS2, CHOP, SHREB, ATF4, and NF-kB; Jazwinski, 2014;Cardamone et al, 2018) that rapidly accumulate in the nucleus in response to stress.…”
mentioning
confidence: 99%